Lewy Body Pathology and Chronic Traumatic Encephalopathy Associated With Contact Sports. Issue 9 (25th July 2018) - Adams, Jason W; Alvarez, Victor E; Mez, Jesse; Huber, Bertrand R; Tripodis, Yorghos; Xia, Weiming; Meng, Gaoyuan; Kubilus, Caroline A; Cormier, Kerry; Kiernan, Patrick T; Daneshvar, Daniel H; Chua, Alicia S; et al.
Abstract: Traumatic brain injury has been associated with increased risk of Parkinson disease and parkinsonism, and parkinsonism and Lewy body disease (LBD) can occur with chronic traumatic encephalopathy (CTE). To test whether contact sports and CTE are associated with LBD, we compared deceased contact sports athletes (n = 269) to cohorts from the community (n = 164) and the Boston University Alzheimer disease (AD) Center (n = 261). Participants with CTE and LBD were more likely to have β-amyloid deposition, dementia, and parkinsonism than CTE alone (p < 0.05). Traditional and hierarchical clustering showed a similar pattern of LBD distribution in CTE compared to LBD alone that was most frequently neocortical, limbic, or brainstem. In the community-based cohort, years of contact sports play were associated with neocortical LBD (OR = 1.30 per year, p = 0.012), and in a pooled analysis a threshold of >8 years of play best predicted neocortical LBD (ROC analysis, OR = 6.24, 95% CI = 1.5–25, p = 0.011), adjusting for age, sex, and APOE ɛ4 allele status. Clinically, dementia was significantly associated with neocortical LBD, CTE stage, and AD; parkinsonism was associated with LBD pathology but not CTE stage. Contact sports participation may increase risk of developing neocortical LBD, and increased LBD frequency may partially explain extrapyramidal motor symptoms sometimes observed in CTE.